The talent and its relation with some changes for the Kindergarten children (Journal of the College of Education for Women, 2019)
Abstract:The current research aims to distinguish the talent for the kindergartenchildren and its relation with some changes . The research included ( 170 )child (male , female ) from the kindergarten children on the year 2009 – 2010the researcher had used PRED meter to achieve the goals of this researchafter being sure from the honesty and the prove and the ( person ) connectioncoefficient had been used to discover the relation between the talent and thechanges which had been mentioned in the research . The result proved thatthe children had talents the toys and the educational scientifically scholarshipfinally the researcher had presented some recommendations and suggestionsfor other studies .